Analysis of the Relationship Between Academic Information Needs and Student Information Search Behavior at the Padjadjaran University Repository - Giriwarna, Rengganis; Prijana, Prijana; Rohman, Asep Saeful (Edulib, 2023)
Developments in the field of library technology, especially in the storage and dissemination of information, have also encouraged institutional awareness to increase their information resource assets. The Padjadjaran University Repository functions as a means of storing, preserving and making accessible sources of information on research that has been prepared by the academic community. Students need scientific sources in the process of completing their coursework, they carry out various stages in searching for appropriate information in their own way. This research aims to determine academic information needs and student information seeking behavior at the Padjadjaran University Repository. The data analysis technique used is descriptive analysis and Pearson Product Moment correlation analysis. Based on the processed data, it was found that the concept of academic information needs has a significant relationship with information seeking behavior. The Padjadjaran University repository is able to provide valid information and can be used as reference material for lecture assignments to students as users. This is because the Padjadjaran University Repository is considered by students to have provided sufficient information based on the form, method of presentation and scope.